Perancangan User Interface Website Essential Clean dengan Menggunakan Metode Human Centered Design (HCD) - Miftachul Bachruddin; Hanifah Muslimah Az-Zahra; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Essential Clean is a business in the field of shoe washing and repair services that was established in 2020. So far, the business management process has been carried out online with social media platforms and offline for the Malang market. Since the entry into force of the lockdown until the PPKM, this business has been greatly affected, so the service process offered must be done online. Some of the problems faced by Essential Clean include the frequent occurrence of human errors due to personal and business chats that are not separate, the waiting time for admins to respond to orders ranges from 30 minutes - 2 hours in busy conditions and the limited number of admins and those who manage orders consist of one admin. Based on the problems that arise, the user interface for the Essential Clean website will then be developed based on the existing problems. With the construction of a website user interface, it is hoped that the order processing process will be more effective, efficient and easy to use. The process of developing this user interface uses the Human-Centered Design method, which involves the user at every stage and can produce a design solution that is specifically built to meet the needs of the related user. The stages of Human-Centered Design are understanding and determining the context of use, determining user requirements, producing a solution design and evaluating the solution design. The evaluation was carried out using a usability testing approach to eight participants. From testing on the aspect of effectiveness, the success rate is 93.06%. The efficiency aspect is carried out by calculating time-based efficiency which produces a value of 0.117 goals/sec. in the aspect of satisfaction measured using the usability scale sistem, it obtained an average value of 89.1, then the value obtained was converted into the SUS score category with adjective ratings excellent and the grade scale got a B value, which means the solution design results are acceptable. From the results of the evaluation, one suggestion was also obtained by the user which was then made improvements to the design of the solution.